Untargeted Metabolomics Analysis Reveals the Effect of Fixation on the Profile of Volatile Compounds of Cyclocarya paliurus Tea - Minge Bai; Liling Wang (Polish Journal of Food and Nutrition Sciences)
Fixation is a necessary tea processing step that affects the quality of tea, including its aroma. However, there are no guidelines to follow whether the Cyclocarya paliurus leaves need to be fixated to produce tea. The aim of this study was to determine the volatile metabolites in fixated and unfixated C. paliuru s tea by gas chromatography-mass spectrometry in order to identify the volatile compounds that differentiate them and establish the key aroma compounds. Compared with the unfixated tea, the fixated tea had higher contents of amines, phenols, nitrogen compounds, ether, alcohol, terpenoids, ester and aromatics. A total of 147 metabolites that differentiated both types of teas were identified using principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA). Among them, 22 and 25 volatile compounds of teas processed without and with fixation, respectively, had relative odor activity values greater than 1. These metabolites had green, fruity, sweet, woody, herbal, floral, fresh, spicy, earthy and waxy odor. This study showed that fixation technology improved the quality of C. paliurus tea, which provided the basis for the production of C. paliurus tea, and promoted the standardization of the preparation technology of C. paliurus tea.